TRANSFORMATION OF BUSINESS MODELS OF ELECTRONIC BUSINESS IN CONDITIONS OF UNSTABLE EXTERNAL ENVIRONMENT - A. V. Trachuk (Real Economics Publishing House, 2015)
The main features of formation of business models in e-business, their typology and possible transformations in the context of a shrinking market are considered in the article. Upon the analytical research, the main components and characteristics of business models of electronic business in various clusters of business models are highlighted. The marking of clusters of business models allows establishing of possible ways of their transformation in the contest of economic uncertainty.